Morphological characterization of newborns in Kinshasa, DR Congo: Common variants, minor, and major anomalies. Issue 4 (7th January 2020) - Mubungu, Gerrye; Lumaka, Aimé; Mvuama, Nono; Tshika, Dahlie; Makay, Prince; Tshilobo, Prosper Lukusa; Devriendt, Koenraad
Abstract: The evaluation of minor physical variation is crucial in a dysmorphological examination. Currently, data on the spectrum and incidence of minor physical variants in Central African newborns is lacking. We therefore conducted a cross‐sectional descriptive study of 722 newborns recruited within the first 24 hr of life, in two large maternities in Kinshasa, DR Congo. Minor anomalies were defined according to the series of articles in AJMG Part A and coded as human phenotype ontology terms. A total of 97 different morphological variants were recorded of which 13 were common. About 34.8% of the newborn carried one minor anomaly, 11.6% had two, and 4.3% had three minor anomalies. No gender differences were observed, but the incidence of specific anomalies appeared to vary with the geographical origin of parents within the DR Congo. The results of this study will aid clinicians to interpret morphological variation in Central African newborns.